(untitled) (Comparatismi, 2019)
L’autore propone alcune riflessioni in dialogo con Return to Literature. A Manifesto in Favour of Theory and against Methodologically Reactionary Studies (Cultural Studies etc.) di Giovanni Bottiroli. The author presents some reflections in dialogue with Return to Literature. A Manifesto in Favour of Theory and against Methodologically Reactionary Studies (Cultural Studies etc.), by Giovanni Bottiroli.